Gamified software application in Teleinformatics class - Veloz Morales, Dargel (2020)
When facing evaluations in the Teleinformatic subject, it is common for students to present difficulties demonstrating the fulfillment of the objectives. Frequent evaluations become an effective tool in the hands of teachers to promote the consolidation of knowledge and the development of skills. However, the teaching load and the tendency towards finalism in students cause little systematization in the study of the subject and therefore poor results in frequent evaluations. Taking into account the existing technological development and the constant linkage of students to ICT, a guide for the design and application of an evaluative instrument for frequent evaluation combined with a computer system is proposed in this work, thus involving novelty and motivation in students through gamification techniques.